A Mathematical Model for the Dynamics of Banditry and Government Intervention in Kaduna State, Nigeria. (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This study developed and analyzes a mathematical model to examine the effect of government policies on the containment of banditry in Kaduna State. Building on the existing model, the model extends existing approaches by incorporating additional compartments such as rehabilitation individuals, security agents and bandit sponsors to better capture real-world dynamics of banditry and intervention mechanisms. A system of nonlinear ordinary differential equations is formulated to describe the interactions among population groups and qualitative analyses including existence and uniqueness of solutions, positivity, invariant region, and banditry-free equilibrium are carried out to ensure the mathematical validity and stability of the model. The analysis reveals that the solutions remain non-negative and bounded within a biological feasible region, confirming the consistency and stability of the system. In addition, the findings show that integrated government policies involving effective security enforcement, rehabilitation programs, rehabilitation programs, intelligence gathering, and disruption of sponsor networks significantly reduce he growth and persistence of banditry. The study highlights the importance of coordinated and sustained intervention strategies in addressing insecurity in Kaduna State and demonstrates the usefulness of mathematical modelling as a predictive and policy-evaluation tool for combating banditry and related criminal activities in Nigeria. and policy-evaluation tool for combating banditry and related criminal activities in Nigeria.